A Statistical Model for the Identification of Key Sectors in I-O Models - Marco Percoco (European Regional Science Association (ERSA), 2004)
Following the seminal work by Bullard and Sebald [Effects of Parametric Uncertainty and Technological Change on In put-Out put Models, Rev. of Ec. And Stat., vol. 59,75-81], in this paper we present an innovative approach to sensitivity analysis in Input-Out put model. In particular, we propose a statistical model capable to compute a sensitivity index associated to each technical coefficient. We call the ordered set of these indices Importance Matrix. Finally, in order to show a simple example for this methodology, we consider the case of the Chicago economy. Keywords: Input-Out put Models, Sensitivity Analysis, Importance Matrix JEL Classification: C15, C67, D5
Keywords: C15; C67; D5; 330; Input-Out put Models; Sensitivity Analysis; Importance Matrix